A comparative evaluation of effectiveness of InGaAsP laser and therapeutic ultrasound administration before the induction of muscle fatigue on healthy young individuals: A clinical study - Roopam Saini; Upasana Sethi Ahuja; Nidhi Puri; Chinthalapalli Siva Ram; Manu Dhillon; Akshay Rathore (Wolters Kluwer Medknow Publications, 2021)
Background: Muscle fatigue or the inability to maintain muscle strength is a protective mechanism to prevent muscle injury. Phototherapy or low-level laser therapy (LLLT) and therapeutic ultrasound are non-invasive and non-pharmacological forms of treatment modalities that have demonstrated effective and affirmative results when used to prevent muscle fatigue. Aim: The study evaluated the effect of phototherapy and therapeutic ultrasound in reducing muscle fatigue when administered before the induction of fatigue. Methodology: The study design was a blind, randomized, and sham-controlled clinical trial on laser and therapeutic ultrasound. The study sample consisted of 100 healthy young participants randomly allocated to four different groups of lasers, sham laser, therapeutic ultrasound, and sham ultrasound. All the individuals were subjected to clinical examination to record the bite force by the bite force dynamometer, maximum interincisal distance (MID) by using digital vernier calipers, and muscle fatigue by using EMG Retrainer's Device. The laser and therapeutic ultrasound were given on the masseter and anterior temporalis muscle on both sides and both sham groups were submitted to the same procedure but with the devices in the switch-off mode. All the individuals were instructed to chew two pieces of gum (one on each side) for 6 min to induce muscle fatigue and MID, the bite force and muscle fatigue were re-evaluated. Results: Statistically significant improvement was observed between the pre-and post-bite force, MID, and muscle fatigue in both the laser and Therapeutic ultrasound group as compared to the sham control groups with the P-value equal to 0.000. No, statistically significant difference was observed in the improvement of the muscle fatigue when both the treatment groups, i.e., laser and therapeutic ultrasound were compared with a P value >0.05. Conclusion: Muscle fatigue can be effectively reduced if any one of the physical modalities, either laser or therapeutic ultrasound is administered before the long-duration treatments; enabling administration of treatment comfortably and effectively in one appointment.